First, subtract 2/3 from both sides and you get
Then multiply both sides by 6/5 and you get
Answer:
3 might be wrong
Step-by-step explanation:
2
(✓7) - 4x4=9
✓9
3
Work shown above! Answer is
a = 144
b = 67
F(x) = 4x - 9
let f(x) = y, this implies that x = f⁻¹(y)
y = 4x - 9 Let us solve for x.
4x - 9 = y
4x = y + 9
x = (y + 9)/4
Recall that x = f⁻¹(y),
x = (y + 9)/4
f⁻¹(y) = (y + 9)/4
That means that for f⁻¹(x)
f⁻¹(x) = (x + 9)/4
Hope this explains it.
Mhm thats most definitely a trick question .